A Survey of Lifelong Learning Policy Implementation in Mongolia: Example of National Literacy Education Program - Oyun, Tsengelbaatar; Dorjpalam, Naranchimeg; Yaish, Shiilegmaa (Lavai - International Journal of Education, 2025)
The concept of lifelong learning encompasses a wide range of learning types, including formal, informal and non-formal learning. It also includes the skills, knowledge, attitudes and behaviors that people acquire through their day-to-day experiences. In this study, we examined current status of lifelong learning policy implementation and stakeholders involved in its execution using various methods. We selected and analyzed the “National Literacy Education Program” to examine current status of lifelong learning policy implementation. We collected and used the secondary sources data from previously published works. Subsequently, we surveyed a total of 93 educators from lifelong learning centers in Mongolia through the questionary to examine stakeholders’ involvement in policy implementation. According to our findings, we highlight that consistency of government's policy on lifelong learning is crucial for its development and for improving the public accessibility. Additionally, stakeholder engagement, teacher leadership and stakeholder opinions positively influence the increased involvement of stakeholders in the implementation of lifelong learning policies.